1992
DOI: 10.1172/jci115706
|View full text |Cite
|
Sign up to set email alerts
|

Human natural anti-Gal IgG regulates alternative complement pathway activation on bacterial surfaces.

Abstract: One percent of circulating IgG in humans recognizes galactose al,3 galactose residues (anti-Gal) and is synthesized in response to stimulation by enteric bacteria. In this study, we found that the prevalence of binding of anti-Gal to blood isolates is significantly higher than its binding to normal stool isolates. When anti-Gal bound onto the lipopolysaccharide of a representative blood isolate, Serratia marcescens #21, it blocked its alternative complement pathway (ACP) lysis and made the organism serum resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 46 publications
4
91
2
Order By: Relevance
“…In humans, ␣Gal-specific Abs are encoded for by a restricted set of Ig Vh genes from the V H 3 family (14). Production of Abs specific for ␣Gal is believed to be elicited in response to normal bacterial flora that colonize the human gastrointestinal tract (11,15). The presence of anti-␣Gal Ab in serum and secretory fluids, such as colostrum and saliva, suggests that these Abs have evolved to play a protective role in primate immunity.…”
mentioning
confidence: 99%
“…In humans, ␣Gal-specific Abs are encoded for by a restricted set of Ig Vh genes from the V H 3 family (14). Production of Abs specific for ␣Gal is believed to be elicited in response to normal bacterial flora that colonize the human gastrointestinal tract (11,15). The presence of anti-␣Gal Ab in serum and secretory fluids, such as colostrum and saliva, suggests that these Abs have evolved to play a protective role in primate immunity.…”
mentioning
confidence: 99%
“…Production of natural Abs specific for ␣Gal is thought to occur following exposure to bacteria that colonize the gastrointestinal tract (7,8). The presence of these Abs in serum and secretory fluids, such as colostrum and saliva, suggests that these Abs have evolved to play a protective role in primate immunity.…”
mentioning
confidence: 99%
“…While the linkage region between PS-2 and peptidoglycan has not been identified yet, PS-2 as well as many other bacterial cell wall polymers is presumed to link to the muramic acid 6-phosphate of peptidoglycan through a phosphodiester linkage, because the purified cell walls contained only glucose, galactose, and peptidoglycan components, except for a slight level of fatty acid. Recently, human natural antigalactosyl antibody has been reported to interact with some bacteria isolated from human flora (6,8). We have found that B. infantis cell walls activate the alternative pathway of human complement system and that this ability of the cell walls is abolished by removing the polysaccharides (unpublished experiments), suggesting that the cell wall polysaccharides react with the antibody.…”
mentioning
confidence: 71%